The Effects of Antenatal Education on Level of Exclusive Breastfeeding in the First Two Months - Gokceoglu, Sonay; Koruk, Ibrahim; Beyaz, Emine (Marmara Univ, Inst Health Sciences, 2024)
Objective: Breastfeeding is a wonderful event that requires strength and dedication from mothers. Effective breastfeeding education provided to pregnant women in the prenatal period can increase the success and level of breastfeeding. This study aimed to determine the effect of prenatal education intervention on the first two-month exclusive breastfeeding level. Method: This experimental study was carried out at a primary family health center between July 2019 and February 2020. One hundred thirty-three pregnant women were included in the study's control and intervention groups. The Prenatal and postnatal information form, the Infant Feeding Attitude Scale (IIFAS) and the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF) were used to collect the data. Results: The first two-month exclusive breastfeeding level was 33.1% in the control group and 68.7% in the intervention group (p <.05). The exclusive breastfeeding status in the first two months was adversely affected 10.5 times by feeding food other than breast milk as the first food after birth, 4.3 times by using pacifier-bottles, and 2.8 times by not receiving breastfeeding education. The weekly progression of the gestational week had a positive effect by 1.6 times, and each unit increase in the number of daily breastfeeding had a positive effect of five times p<.05) Conclusion: Prenatal breast milk and breastfeeding education increased the first two-month exclusive breastfeeding level. The education also had a positive effect on daily breastfeeding frequency, pacifier-bottle use, night breastfeeding levels and water use.
Keywords: Pregnancy; prenatal breastfeeding education; effect on breastfeeding